2021
DOI: 10.3390/pr9071090
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Heterotrophic Microalgae in Waste Conversion to Biofuels and Bioproducts

Abstract: In the last few decades, microalgae have attracted attention from the scientific community worldwide, being considered a promising feedstock for renewable energy production, as well as for a wide range of high value-added products such as pigments and poly-unsaturated fatty acids for pharmaceutical, nutraceutical, food, and cosmetic markets. Despite the investments in microalgae biotechnology to date, the major obstacle to its wide commercialization is the high cost of microalgal biomass production and expensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…In many researches, it has been demonstrated that wastewater and by‐products obtained from industries contains particles or have dark color that prevents adequate light penetration necessary for microalgae growth (Silva et al, 2021). The positive effect of NaNO 3 was observed in Figure 2 where the lipid productivity increased as NaNO 3 concentration in the blends increased.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In many researches, it has been demonstrated that wastewater and by‐products obtained from industries contains particles or have dark color that prevents adequate light penetration necessary for microalgae growth (Silva et al, 2021). The positive effect of NaNO 3 was observed in Figure 2 where the lipid productivity increased as NaNO 3 concentration in the blends increased.…”
Section: Resultsmentioning
confidence: 99%
“…It roughly contains 40%–50% sugar such as sucrose and fructose and is rich in microelements (e.g., Ca 2+ , Mg 2+ , K + , and Fe 2+ ) (Caballero et al, 2003; Yan et al, 2011). So, it can provide large amounts of nutrients for microalgae growth (Silva et al, 2021; Yew, Puah, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A total nitrogen removal efficiency of 94.45%, 0.241 g/L lipid production and biomass production of 1.42 g/L was attained in synergistic microalgal-bacterial incorporation in wastewater remediation (Leong et al, 2019). It was estimated that glucose derived biodiesel costs USD $3.79/L whereas agriculture waste and food waste derived biodiesel costs USD $2.6-3.0/L and $0.6/L (Silva et al, 2021).…”
Section: Geobacillusmentioning
confidence: 99%
“…Heterotrophic and mixotrophic conditions exhibit higher biomass yield, extended exponential phase of growth, and less biomass loss [96]. Under mixotrophic conditions, both inorganic and organic carbon can be assimilated under certain operational conditions to increase biomass productivity and other high-value byproducts [97,98]. For example, Kujawska et al, 2021 [99], demonstrated waste glycerol as a potential organic carbon source to reach a Schizochytrium sp.…”
Section: Cultivation (Photobioreactors and Growth Conditions)mentioning
confidence: 99%